Pengaruh Metode Pembelajaran Authentic Material Terhadap Hasil Belajar Bahasa Arab Siswa - Fajriyani Arsya; Loli Safitri (Jurnal Educative: Journal of Educational Studies, 2019)
This study is quasi-experimental research which aims to determine the effect of authentic material on student learning outcomes on Arabic Language subjects at grade VIII MTsN 6 Agam. The sample of this study was taken using purposive sampling, namely class VIII.1 as the control class and class VIII.2 as the experimental class. The results of the statistical analysis showed that the posttest means score for the experimental group students was 74.00 and the control group was 64.63. Then, hypothesis testing was done using the t-test at the 95% confidence level (α = 0.05). The two similarity test results were carried out to determine whether there were significant differences between the mean scores of the pretest and posttest of the control class and the experimental class. Then it was obtained that t-count> t-table which is equal to 2.484> 2,000 and Sig. (2-tailes) of 0.16> 0.05. Then, according to the basis of decision making in the Independent Sample T-Test, it can be concluded that Ho is rejected and Ha is accepted. It means that there is a significant difference between the average student learning outcomes in the experimental class compared to the control class. In other words, there is a significant effect of using authentic material on the Arabic language learning outcomes of students in theالسَّاعَةُmaterial (time) in class VIII MTsN 6 AgamPenelitian inimerupakan eksperimen semu (Quasy Eksperiment) dengan desain Non equivalent control group design,yang bertujuan untuk mengetahui pengaruh terhadap hasil belajar siswa pada mata pelajaran Bahasa Arab yang diajar menggunakan metode pembelajaran authentic material kelas VIII MTsN 6 Agam.Sample penelitian ini diambil dengan menggunakan purposive sampling yaitukelasVIII.1 sebagai kelas control dan kelas VIII.2 sebagai kelas eksperimen. Hasil analisis sttistik menunjukkan bahwa nilai rata-rata posttest untuk siswa kelompok eksperimen sebesar 74,00dan kelompok kontrol sebersar 64,63. Kemudian, dilakukan pengujian hipotesis yang  menggunakan uji-t pada taraf kepercayaan 95%(α=0.05). Hasil yang diperoleh dari uji kesamaan dua rata-ratadilakukan bertujuanuntuk mengetahui apakah terdapat perbedaan yang signifikan antara mean skor dari pretest dan posttest kelas kontrol dan kelas eksperimen. Makadiperoleh nilai dimanathitung> ttabelyaitu sebesar 2,484 > 2,000 dan  Sig.(2-tailes) sebesar 0,16 > 0,05, maka sesuai dasar pengambilan keputusan dalam Uji Independent Sample T-Test dapat disimpulkan bahwa Ho ditolak dan Ha diterima, yang artinya bahwa terdapat perbedaan yang significant antara rata-rata hasil belajar siswa di kelas eksperimen dibanding di kelas kontrol. Dengan kata lain ada pengaruh penggunaan metode pembelajaran authentic material terhadap hasil belajar bahasa arab siswa pada materi السَّاعَةُ (waktu) di kelas VIII MTsN 6 Agam.